Characterization of V. cholerae O1 biotype El Tor serotype Ogawa possessing the ctxB gene of the classical biotype isolated from well water associated with the cholera outbreak in Kerala, South India - P. S. Reethy; K. V. Lalitha (IWA Publishing, 2021)
We investigated 22 water samples (17 well water and five pipe water - both chlorinated) and six soil samples from the surroundings of wells of the households of suspected patients from Palakkad district, Kerala (India), from where a cholera outbreak was reported during June-July 2016. A total of 25 Vibrio cholerae isolates were collected from three well water samples during a recent cholera outbreak. Biochemical and serological studies revealed that all of the isolates belonged to serogroup O1, biotype El Tor, serotype Ogawa. PCR assays confirmed the occurrence of ctxB, ctxA, hlyA, tcpA El Tor,VPI, ace, zot, ompW, rfbO1 and toxR genes in all isolates. The presence of the ctxB gene of the classical biotype in all of the El Tor isolates suggests that it is a new variant of El Tor biotype. Antibiogram profile of all V. cholerae O1 isolates revealed resistance towards five classes of antibiotics island and indicates that they were multidrug resistant. ERIC-PCR and PFGE finger prints showed the clonal relationship among the V. cholerae O1 isolates. The results of this study revealed the emergence of a new variant of El Tor biotype in the water samples from Palakkad district, from where a cholera outbreak was reported. HIGHLIGHTS Presence of altered V. cholerae O1 El Tor Ogawa strains in chlorinated well water might constitute a threat to public well-being.; Isolated strains with virulent genes have potential to become pathogenic.; Multidrug resistant strains have shown antibiotic resistance towards commonly used antibiotics.; This research will be useful in ecological and epidemiological studies.;